MOBSTER – IV. Detection of a new magnetic B-type star from follow-up spectropolarimetric observations of photometrically selected candidates★. Issue 4 (1st April 2021) - David-Uraz, A; Shultz, M E; Petit, V; Bowman, D M; Erba, C; Fine, R A; Neiner, C; Pablo, H; Sikora, J; ud-Doula, A; Wade, G A
ABSTRACT: In this paper, we present results from the spectropolarimetric follow-up of photometrically selected candidate magnetic B stars from the MOBSTER (Magnetic OB[A] Stars with TESS : probing their Evolutionary and Rotational properties) project. Out of four observed targets, one (HD 38170) is found to host a detectable surface magnetic field, with a maximum longitudinal field measurement of 105 ± 14 G. This star is chemically peculiar and classified as an α 2  CVn variable. Its detection validates the use of the Transiting Exoplanet Survey Satellite ( TESS ) to perform a photometric selection of magnetic candidates. Furthermore, upper limits on the strength of a putative dipolar magnetic field are derived for the remaining three stars, and we report the discovery of a previously unknown spectroscopic binary system, HD 25709. Finally, we use our non-detections as case studies to further inform the criteria to be used for the selection of a larger sample of stars to be followed up using high-resolution spectropolarimetry.